2023
DOI: 10.1186/s12967-023-04015-8
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid inhibits cell growth in both MCF-7 and MDA-MB231 cells by triggering different responses in a cell type-specific manner

Abstract: Background Breast cancer is the second leading cause of death among women after lung cancer. Despite the improvement in prevention and in therapy, breast cancer still remains a threat, both for pre- and postmenopausal women, due to the development of drug resistance. To counteract that, novel agents regulating gene expression have been studied in both hematologic and solid tumors. The Histone Deacetylase (HDAC) inhibitor Valproic Acid (VA), used for epilepsy and other neuropsychiatric diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…MCF-7 cells and MDA-MB-231 cell were subjected to treatments with 6 and 37 to corroborate these compounds’ ability to inhibit cell proliferation. Outlined above, MCF-7 (ER and PR ( +) and MDA-MB-231 (ER, PR, and HER2 (−) cell lines were considered as models of the most common and aggressive subtype of breast cancer according to their molecular expression pattern, in addition to a deregulated Bcl-2 activity promoting an anti-apoptotic effect 62 , 63 . As is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MCF-7 cells and MDA-MB-231 cell were subjected to treatments with 6 and 37 to corroborate these compounds’ ability to inhibit cell proliferation. Outlined above, MCF-7 (ER and PR ( +) and MDA-MB-231 (ER, PR, and HER2 (−) cell lines were considered as models of the most common and aggressive subtype of breast cancer according to their molecular expression pattern, in addition to a deregulated Bcl-2 activity promoting an anti-apoptotic effect 62 , 63 . As is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the MDA-MB 231 are triple-negative cancer cells (-ER/- PR/- E-Catherin) in which, the protein have mutated, suggesting that the difference in anti-proliferative efficacy between the tested cell lines could be attributable to one of these pathways. In the case of MDA-MB-231 cells, the growth-inhibiting effects of phytoestrogens may be mediated through the modulation of multiple signalling pathways, including the extracellular matrix (ECM), adhesion, cell cycle, chemokine and cytokine, PI3K/AKT, STAT, TGF-β, MAPK, NF-κB, RAS/Rho, DNA repair, and apoptosis signals ( Giordano et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Giordano et al demonstrated that VPA inhibits the proliferation of MDA-MB 231 and MCF-7 cells by arresting the cell cycle at the G0/G1 phase through the generation of ROS from mitochondria. Furthermore, VPA induces apoptosis by releasing cytochrome c and activating poly (ADP-ribose) polymerase (PARP), achieved through the downregulation of Bcl2 and the upregulation of Bax and Bad [78]. In a separate study, Injinari et al experimentally demonstrated that VPA induces apoptosis in MDA-MB-231 and MCF-7 cells by reducing the expression of HDAC by increasing the expression of miR-34a and 520 h. Additionally, VPA elicited cytotoxicity in these cells by enhancing lipid peroxidation [79].…”
Section: Sensitization Of Bc Cells With Antiepileptic Drugsmentioning
confidence: 99%